ӘДЕБИЯТ САБАҚЛАРЫНДА Т.ҚАЙЫПБЕРГЕНОВТЫҢ «МУҒАЛЛИМГЕ РАХМЕТ» ПОВЕСТИН ОҚЫТЫЎ УСЫЛЛАРЫ - Қалбаева, Г.; Алламбергенова, М. (SCIENCE and SOCIETY, 2021)
The article is devoted to the tasks facing the teacher in the process of teaching in literature lessons the narration of T.Kayipberganov "Thanks to Teacher", and also gave recommendations on effective methods and techniques of literary education, including the method of oral and written teaching (narration, description of the hero, retelling of a literary text, essay), interpretation of a literary text, question-answer, Brainstorming (kkk method know, knew, will know).
Keywords: literary teaching; method; reception; text analysis; oral and written exercise